Music in the Air. - Gleason, Ralph J. (Yale University Press, 2016)
This sterling anthology, edited by Gleason's son Toby, himself a forty-year veteran of the music business, spans Ralph J. Gleason's four decades as popular music's preeminent commentator. Drawing from a rich variety of sources, including Gleason's books, essays, interviews, and LP record album liner notes, it is essential reading for writers, historians, scholars, and music lovers of every stripe.